2022
DOI: 10.1177/20406207211072838
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of mesenchymal stem cells treatment for multidrug-resistant graft-versus-host disease after haploidentical allogeneic hematopoietic stem cell transplantation

Abstract: Purpose: Graft- versus-host disease (GVHD) is an important complication after human leukocyte antigen (HLA) haploidentical donor (HID) hematopoietic stem cell transplantation (HSCT), which may lead to poor prognosis. Our study intends to identify the efficacy and safety of mesenchymal stem cells (MSCs) for multidrug-resistant (MDR)-GVHD after HID HSCT. Methods: MDR-GVHD was referring to GVHD remaining no response to at least two types of therapy, and hUCB-MSCs were given at the dose of (1.0–2.0) × 106/kg once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Several studies have reported that low‐dose methotrexate treatment was tolerable and effective for GVHD 33–35 . The safety of mesenchymal stem cell infusion for SR‐aGVHD was acceptable, 36,37 although its efficacy was controversial 38–41 . Thus, whether these two methods could further improve the efficacy of basiliximab treatment is of the utmost interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that low‐dose methotrexate treatment was tolerable and effective for GVHD 33–35 . The safety of mesenchymal stem cell infusion for SR‐aGVHD was acceptable, 36,37 although its efficacy was controversial 38–41 . Thus, whether these two methods could further improve the efficacy of basiliximab treatment is of the utmost interest.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] The safety of mesenchymal stem cell infusion for SR-aGVHD was acceptable, 36,37 although its efficacy was controversial. [38][39][40][41] Thus, whether these two methods could further improve the efficacy of basiliximab treatment is of the utmost interest.…”
Section: Optimal Protocols For Basiliximab Treatmentmentioning
confidence: 99%
“…Thus far, there are many clinical studies focused on ruxolitinib for SR-GVHD treatment, and Li et al (19) had conducted a meta-analysis for ruxolitinib as the treatment for SR-GVHD in adults; however, only studies published before January 2019 were enrolled. Since 2019, many important research studies for ruxolitinib in SR-GVHD have been published (15,16,(20)(21)(22)(23)(24)(25)(26)(27)(28). In addition, this meta-analysis did not include children, whereas several studies focused on ruxolitinib for treatment of SR-GVHD in children have been published since 2019 (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…ATG, cyclosporine A (CSA), mycophenolate mofetil, and short-term methotrexate were administered to prevent GVHD ( Supplementary Methods ) ( Wang et al., 2019 ). Protocol for GVHD and minimal residual disease therapy had been reported in detail ( Liu et al., 2020 ; Zhao et al., 2021 ; Fan et al., 2021 ; Shen et al., 2021 ; Mo et al., 2022 ; Shen et al., 2022 ; Shen et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%